Dysleksja rozwojowa w kontekście edukacji obcojęzycznej – perspektywa interdyscyplinarna - Jaworska-Biskup, Katarzyna (Neofilolog, 2011)
Many branches of science and academic disciplines such as psychology, linguistics or medicine fuel interest in developmental dyslexia by propos-ing a variety of theories attempting to determine what causes dyslexia and how dyslexia influences the acquisition of a foreign. For this particular reason, a foreign language teacher must not only be equipped with a sound methodological knowledge but also familiar with current ap-proaches to dyslexia. The main tenet of this article is that dyslexia-related difficulties have a tremendous impact on second language learning, which necessitates the inclusion of specially adapted techniques and instruction.